(untitled) (Eurasian Journal of Ecology, 2025)
Bacterial cellulose is a microbial biopolymer that serves as an alternative to plant-derived cellulose, distinguished by its high purity, crystallinity, and biocompatibility. The structural and functional properties of this material enable its application in various fields such as medicine, food packaging, textiles, and composite materials. This study describes the main microbial strains and nutrient media used in bacterial cellulose production, as well as the potential use of agricultural and industrial waste as carbon sources. Purification methods (alkaline treatment, surfactants, enzymatic, and physical approaches) are comparatively reviewed in terms of efficiency, environmental impact, and suitability for end-use applications. The comparative analysis indicates that selecting appropriate carbon sources and microbial strains, along with optimizing purification methods, can enhance production yield and cellulose purity. The adoption of biodegradable reagents and zero-waste technologies plays a critical role in improving the sustainability of bacterial cellulose production. This review systematically explores technological solutions and future directions necessary for industrial-scale applications of bacterial cellulose, considering life cycle assessment, environmental safety, production costs, and end-use requirements. Keywords: bacterial cellulose; purification methods; production efficiency; environmental sustainability; application fields